Ответ:
1) x=-1,1
2)x=5
3)![x=\frac{\pi}{4}+\frac{\pi{k}}{2},k\in\mathbb Z x=\frac{\pi}{4}+\frac{\pi{k}}{2},k\in\mathbb Z](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B%5Cpi%7D%7B4%7D%2B%5Cfrac%7B%5Cpi%7Bk%7D%7D%7B2%7D%2Ck%5Cin%5Cmathbb%20Z)
Пошаговое объяснение:
0\\6t^2-13t+6=0\\t_{1,2}=\frac{13\pm\sqrt{169-4*6*6}}{12}=\frac{13\pm\sqrt{25}}{12}=\frac{3}{2};\frac{2}{3}\\(\frac{2}{3})^x=\frac{3}{2}\\x=-1\\(\frac{2}{3})^x=\frac{2}{3}\\x=1" alt="1)\\6*4^x+6*9^x=13*6^x\\6*2^{2x}+6*3^{2x}-13*2^x*3^x=0\:/:3^{2x}\\6*(\frac{2}{3})^{2x}+6-13*(\frac{2}{3})^x\\(\frac{2}{3})^x=t;\:\:\:t>0\\6t^2-13t+6=0\\t_{1,2}=\frac{13\pm\sqrt{169-4*6*6}}{12}=\frac{13\pm\sqrt{25}}{12}=\frac{3}{2};\frac{2}{3}\\(\frac{2}{3})^x=\frac{3}{2}\\x=-1\\(\frac{2}{3})^x=\frac{2}{3}\\x=1" align="absmiddle" class="latex-formula">
2\\x+4=x^2-4x+4\\x^2-5x=0\\x(x-5)=0\\x=0\\x=5" alt="2)\\\sqrt{x+4}=x-2\\ODZ:\\x>2\\x+4=x^2-4x+4\\x^2-5x=0\\x(x-5)=0\\x=0\\x=5" align="absmiddle" class="latex-formula">
x=0 - посторонний корень
![3)\\\cos^4(2x)-\sin^4(2x)=-1\\(\cos^2(2x)-\sin^2(2x))(\cos^2(2x)+\sin^2(2x))=-1\\\cos(4x)=-1\\4x=\pi+2\pi{k},k\in\mathbb Z\\x=\frac{\pi}{4}+\frac{\pi{k}}{2},k\in\mathbb Z 3)\\\cos^4(2x)-\sin^4(2x)=-1\\(\cos^2(2x)-\sin^2(2x))(\cos^2(2x)+\sin^2(2x))=-1\\\cos(4x)=-1\\4x=\pi+2\pi{k},k\in\mathbb Z\\x=\frac{\pi}{4}+\frac{\pi{k}}{2},k\in\mathbb Z](https://tex.z-dn.net/?f=3%29%5C%5C%5Ccos%5E4%282x%29-%5Csin%5E4%282x%29%3D-1%5C%5C%28%5Ccos%5E2%282x%29-%5Csin%5E2%282x%29%29%28%5Ccos%5E2%282x%29%2B%5Csin%5E2%282x%29%29%3D-1%5C%5C%5Ccos%284x%29%3D-1%5C%5C4x%3D%5Cpi%2B2%5Cpi%7Bk%7D%2Ck%5Cin%5Cmathbb%20Z%5C%5Cx%3D%5Cfrac%7B%5Cpi%7D%7B4%7D%2B%5Cfrac%7B%5Cpi%7Bk%7D%7D%7B2%7D%2Ck%5Cin%5Cmathbb%20Z)